Effect of Temperature and Frequency on the Dielectric Properties of PVC/MnCl2 Composite - Salih, A. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The dielectric properties of polyvinyl chloride (PVC)-MnCl2 composite were studied by using the impedance technique. The measurements were carried out as a function of frequency in the range from 10 Hz to 13 MHz and temperature range from 27oC to 55oC. Using a composite of 20 wt. % MnCl2 by weight, it was found that the dielectric constants and the dielectric loss of the prepared films increase with the increasing temperature at law frequency and the enhancement of the ionic conduction which is confirmed by the increase the of AC. conductivity and the decrease of the activation energy of the conduction mechanism at high applied frequency. The observed relaxation and polarization effects of composite are mainly attributed to the dielectric behavior of the MnCl2 filler and polarity of the polymer PVC. However, the results were explained on the basis of the interfacial (space charge) polarization dipolar polarization and the decrease of the hindrance of the polymer matrix with the ionic mobility and impurities in the composite.